Diagnostics for Yaws Eradication: Insights From Direct Next-Generation Sequencing of Cutaneous Strains of Treponema pallidum. (16th October 2017) - Marks, Michael; Fookes, Maria; Wagner, Josef; Butcher, Robert; Ghinai, Rosanna; Sokana, Oliver; Sarkodie, Yaw-Adu; Lukehart, Sheila A; Solomon, Anthony W; Mabey, David C W; Thomson, Nicholas
Abstract : Yaws is an important cause of skin disease in tropical countries. Using next-generation sequencing, we tested yaws-like ulcers, which were negative using standard molecular diagnostics. We found primer binding site mutations explaining the negative results of the standard assay. Abstract: Background: Yaws-like chronic ulcers can be caused by Treponema pallidum subspecies pertenue, Haemophilus ducreyi, or other, still-undefined bacteria. To permit accurate evaluation of yaws elimination efforts, programmatic use of molecular diagnostics is required. The accuracy and sensitivity of current tools remain unclear because our understanding of T. pallidum diversity is limited by the low number of sequenced genomes. Methods: We tested samples from patients with suspected yaws collected in the Solomon Islands and Ghana. All samples were from patients whose lesions had previously tested negative using the Centers for Disease Control and Prevention (CDC) diagnostic assay in widespread use. However, some of these patients had positive serological assays for yaws on blood. We used direct whole-genome sequencing to identify T. pallidum subsp pertenue strains missed by the current assay. Results: From 45 Solomon Islands and 27 Ghanaian samples, 11 were positive for T. pallidum DNA using the species-wide quantitative polymerase chain reaction (PCR) assay, from which we obtained 6 previously undetected T. pallidum subsp pertenue whole-genome sequences. These show that Solomon Islands sequences represent distinct T. pallidum subsp pertenue clades. These isolates were invisible to the CDC diagnostic PCR assay, due to sequence variation in the primer binding site. Conclusions: Our data double the number of published T. pallidum subsp pertenue genomes. We show that Solomon Islands strains are undetectable by the PCR used in many studies and by health ministries. This assay is therefore not adequate for the eradication program. Next-generation genome sequence data are essential for these efforts.